Seasonal variations in North Atlantic atmospheric river activity and associations with anomalous precipitation over the Iberian Atlantic Margin. Issue 2 (30th January 2016) - Eiras‐Barca, Jorge; Brands, Swen; Miguez‐Macho, Gonzalo
Abstract: In the present study, a novel atmospheric river (AR) detection scheme based on column‐integrated water vapor and column‐integrated water vapor flux is presented and applied for the Iberian Atlantic Margin (IAM) and a wider area covering the North Atlantic Ocean for the period 1979–2013. The seasonal cycle in AR frequency over the North Atlantic exhibits a relatively small amplitude, being more pronounced toward the east and south of the oceanic basin, as it is increasingly related to the seasonal cycle in storm activity and the meridional displacement of the subtropical high. In the eastern North Atlantic, downwind of the North American continent, it shows a more complex behavior. The interannual variability of AR frequency is weak across the entire North Atlantic, and it does not present consistent long‐term spatiotemporal patterns. For the southern IAM, AR occurrence is slightly enhanced by the negative phase of the North Atlantic Oscillation during the previous days. Up to 80% of the anomalous precipitation events (above the 95th percentile) in the IAM are associated with ARs; these values exceed 90% in winter and decrease to 75% in spring when convection not related to ARs becomes a significant precipitation mechanism. Moisture advection within ARs is thus a very important contributor to anomalous precipitation. Likewise, the strength of the associated storm systems and the characteristics of the ARs themselves are also very relevant factors. The percentage of total ARs linked to anomalous precipitation is relatively low, only reaching 20% where topographic features are favorable. Key Points: Up to 90% of anomalous precipitation in western Iberia is linked to ARs This coincidence ratio is largest during winter and lowest in spring AR frequency in western Iberia is highest during the negative phase of the NAO